Efecto del nematicida carbofuran más atrayentes natural en el control de picudo negro (Cosmopolitessordidus) en plátano barraganete y harton. - Mendoza Párraga, Jacinto Ramón (2011)
This researchwas conducted (in thebanana production program) at Finca el Moral Propertyof Mr. Byron Flores Loayza, located at km 58 froadQuevedo-Santo Domingo,ProvinceTsachila, whoselocationis1 °3'18'' south latitudeand79 °25'24'' west longitude at aheightof73meters. Whichlasted120 days, the weatherin the area, temperature24.9°C, humidity 88.0%, precipitation is 2885.5mm, 629 hoursheliophanylightyears. We used 10 traps per plot and 40 traps per treatment was applied completely randomized design with a factorial 3 x 3, Factor Three natural attractant (Pineapple, Molasses and Pseudostem). And Factor B Three doses of carbofuran (15, 20 and 25 cc) and four replicates to determine the difference between middle-range test was used Tukey multiplied with a confidence level of 95%. Experimental measurements The investigation is performed in an area of 20,000 m2, the evaluation of black-weevil control was made between 6H30 to 7H30 am, weevils were sung in every one of the experimental units, evaluations at 7, 14, 21 and 28 days. Number of weevils (males vs. females) per trap.Effectiveness of the attractants. Influence of carbofuran dose. The natural attractant had the highest pseudostem weevil control of adult black hartón silver in all periods and phases evaluated, the pseudostem as attractants at 7 and 14 days has the highest black weevils in the first phase with 76.08 and plantain Harton 62.08 billfish caught, three doses of carbofuran to control banana weevil adult black hartón are statistically equal in all stages and phases evaluated. The smallest adult black weevil control the natural attractant record molasses At 7 and 14 days of evaluation report greater control of black seabream natural attractant Harton plantain, the time for appealing in black weevil control and increases the time will decrease substantially weevil control, the phases adult black weevil control in plantain Harton natural attractant increases the low replica black weevil population, lower cost is presented using pseudostem with three doses of carbofuram in adult black weevil control in plantation of silver does not hartón